2017
DOI: 10.13189/ujph.2017.050403
|View full text |Cite
|
Sign up to set email alerts
|

Is Prior Aspirin Use Associated with Reduced Severity in Patients with Acute Pancreatitis?

Abstract: Clinical severity of Acute Pancreatitis (AP)following the use of Aspirin is inconclusive in previous studies. This study investigated predicting the severity of AP using Ranson criteria at admission and at 48 hours and, the length of hospital stay by prior aspirin use. Medical records of first-presentation AP patients during the five years between 2010 and 2015 were examined in the Goulburn Valley Base Hospital, Victoria, Australia. Uses of aspirin at admission with some co-morbidity, Ranson criteria at admiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…In a study of 192 patients with acute pancreatitis in the USA, aspirin decreased the severity of acute pancreatitis at 24 h and 48 h of admission, based on Ranson's score [7]. Another study in Australia on 245 patients with acute pancreatitis reported that patients with aspirin use had higher Ranson's scores at admission and at 48 h of admission [8]. Although Ranson's score could not be used to assess severity in our study, we used surrogate markers of severity such as ICU admission, shock, in-hospital mortality as well as acute pancreatitis-DRG severity criteria.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study of 192 patients with acute pancreatitis in the USA, aspirin decreased the severity of acute pancreatitis at 24 h and 48 h of admission, based on Ranson's score [7]. Another study in Australia on 245 patients with acute pancreatitis reported that patients with aspirin use had higher Ranson's scores at admission and at 48 h of admission [8]. Although Ranson's score could not be used to assess severity in our study, we used surrogate markers of severity such as ICU admission, shock, in-hospital mortality as well as acute pancreatitis-DRG severity criteria.…”
Section: Discussionmentioning
confidence: 99%
“…A small pilot study in 192 patients revealed aspirin use was associated with decreased severity at 24 h and 48 h in patients with acute pancreatitis [7]. Another study containing 245 patients with acute pancreatitis in Australia revealed that aspirin use was significantly associated with higher Ranson scores, both at admission and at 48 h of admission [8]. On the contrary, some case reports have documented that the use of aspirin over a long period of time may trigger acute pancreatitis [9].…”
Section: Introductionmentioning
confidence: 99%